BUILDING MODEL DESIGN DEFECTS OBJECT ORIENTED SOFTWARE METHOD - Сидоров, М.О.; Нечай, О.С. (Science-based technologies, 2009)
In the paper the notion of object-oriented design defect progress degree is introduced and the method for defect models construction is proposed. Constructed models allow defect degree assessment. Reasons of design defect appearance and development are defined. State description of software element affected by design defect is ac-complished by design rules analysis, metrics normalizing and function building on the base of t-norm and t-conorm. God Class defect model is build and its adequacy is approved by manual code inspection.